Heat Capacity of Sodium Aminoacetate Solutions before and after CO2 Absorption - Harris, F (American Chemical Society, 2010)
The heat capacities of aqueous solutions of sodium aminoacetate (CAS no. 6000-44-8) and CO2-loaded aqueous sodium aminoacetate solutions were measured for a range of sodium aminoacetate mass fractions w ) (0.01, 0.05, 0.10, 0.15, 0.20, and 0.30) and at a temperature range of T ) (298.15 to 323.15) K. It was found that the heat capacity of the aqueous solution of sodium aminoacetate decreases as the concentration increases and increases with an increase in temperature. The heat capacity of CO2-loaded aqueous sodium aminoacetate solution was found to increase with temperature and decrease with an increase in CO2 loading. The heat capacities of the CO2-loaded aqueous sodium aminoacetate solution were lower than those of the unloaded solutions.